Kebijakan Kemaritiman Indonesia : Studi Kasus Pengelolaan Sumber Daya Lumba-Lumba di Pantai Lovina Bali - Dwi Rianingsih; Agussalim Burhanuddin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Lovina Beach, which is located in the northern part of Bali Island, has long been known as one of the main tourist destinations in Bali, especially for tourists who are interested in seeing dolphins in their natural habitat. This tourist attraction has been operating since 1987 and is a major contributor to local tourism. Lovina's dolphins are not only a tourist attraction, but also a symbol of Indonesia's rich marine biodiversity. However, as tourism develops and the number of visitors increases every year, there are increasing concerns regarding the management of dolphin resources in Lovina. Tourism activities that focus on observing dolphins have the potential to have a negative impact on marine ecosystems, especially on the dolphin population itself. Therefore, managing dolphin resources at Lovina Beach is a very important and urgent topic to consider.